Delivery of selenium using chitosan nanoparticles: Synthesis, characterization, and antioxidant and growth effects in Nile tilapia (Orechromis niloticus). - Juliana M Araujo (Public Library of Science (PLoS), 2021)
This study aimed to elucidate the effects of selenium-loaded chitosan nanoparticles used as a dietary supplement on Nile tilapia (Oreochromis niloticus) antioxidant and growth responses. First, chitosan-based nanoparticles containing selenium (Se) were synthesized using the ionotropic gelation method and their physicochemical characteristics, controlled release profile, and antioxidant activity properties were investigated. Thereafter, the effects on glutathione peroxidase and antioxidant activities (by radical scavenging activity), growth, and whole-body composition of Nile tilapia were evaluated when they were fed with Se-loaded chitosan nanoparticles and compared with other selenium dietary supplements. Se-loaded chitosan nanoparticles showed high entrapment efficiency (87%), spherical shape, smooth surface, and broad size distribution. The controlled release of Se consisted of an initial burst followed by a gradual release over 48 h. Se-loaded nanoparticles presented significantly higher antioxidant activity compared to free Se. A 60-day feeding trial was conducted to compare the effects of supplementing different dietary Se sources, including selenomethionine (as organic source), sodium selenite (as inorganic source), and Se-loaded chitosan nanoparticles (Se-Nano and Se-Nano x1.5) on antioxidant and growth responses of Nile tilapia. A basal diet without Se supplementation was used as the control. The dietary supplementations with different Se sources (free and encapsulated selenium) lead to significant improvements in final weight and feed efficiency of Nile tilapia fingerlings. However, dietary treatments did not affect whole-body protein and lipid content. Diets containing Se-Nano and Se-Nano x1.5 were more effective than sodium selenite and selenomethionine in preventing oxidative stress and improving antioxidant activity in Nile tilapia. Overall, Se-loaded nanoparticles presented a great potential as an efficient source for delivering dietary Se to Nile tilapia, directly affecting the growth performance, feed efficiency, oxidative stress, and antioxidant activity of this species.